Molar Incisor Hypomineralization - Takahashi, Karine; Cunha Correia, Adriana de Sales; Cunha, Robson Frederico [UNESP] (Journal Pedodontics Inc, 2009)
Enamel defects are common alterations that can occur in both the primary or permanent dentition. A range of etiological factors related to this pathology can be found in the literature. Molar Incisor Hypomineralization (MIH) is a kind of enamel defect alteration that requires complex treatment solutions, and for this reason, it is of great clinical interest for dental practice. This article describes the management of a clinical case of MIH in a 7-year-old child. The different treatment options depending on the extension of the defect, the degree of tooth eruption and the hygiene and diet habits of the patient are also discussed.
Keywords: dental enamel; dental enamel hypoplasia; permanent teeth